2021
DOI: 10.1177/19400829211065359
|View full text |Cite
|
Sign up to set email alerts
|

Recolonization of Former Range by Endangered BantengBosjavanicusin Mae Wong National Park, Thailand

Abstract: Many large ungulate species, including the banteng ( Bos javanicus), are on the verge of extinction. Mae Wong National Park in Thailand was once a haven for banteng due to its abundance of preferred habitat, but the species was extirpated in the 1970s due to logging and hunting, before park designation. Mae Wong is connected with Huai Kha Khaeng Wildlife Sanctuary (HKK), which retains the largest banteng population remaining in Thailand. In 2019, Mae Wong park rangers reported suspected banteng footprints near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
(6 reference statements)
1
2
0
Order By: Relevance
“…Banteng populations and habitats in Southeast Asian islands (Borneo, Java, and Bali) are threatened due to hunting for horn and meat consumption and habitat loss (Dewi et al, 2020). In Thailand, we found high suitability similar to previous studies in Eastern (Menkham et al, 2019) and Western forest complexes (Jornburom et al, 2020), including reintroduction areas in Salak Pra WS (Chaiyarat et al, 2019) and where recent recolonisation by natural population movement has occurred in Mae Wong NP (Phoonjampa et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…Banteng populations and habitats in Southeast Asian islands (Borneo, Java, and Bali) are threatened due to hunting for horn and meat consumption and habitat loss (Dewi et al, 2020). In Thailand, we found high suitability similar to previous studies in Eastern (Menkham et al, 2019) and Western forest complexes (Jornburom et al, 2020), including reintroduction areas in Salak Pra WS (Chaiyarat et al, 2019) and where recent recolonisation by natural population movement has occurred in Mae Wong NP (Phoonjampa et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…Jornburom et al (2020) simulated a map of predicted occupancy for banteng in WEFCOM in the absence of poaching, and estimated ~6,400 km 2 of ecologically suitable habitat that could support reintroduction of banteng in other protected areas and reports banteng used low elevations and low slopes. Furthermore, Mae Wong National Park confirms the return of banteng after an absence of over 40 years, likely dispersed from HKK (Phoonjampa et al, 2021).…”
Section: Bantengmentioning
confidence: 66%
“…The current results were consistent with those of Paansri et al (2022) and confirmed that the dry evergreen forest at Mun Sam Ngam is a suitable habitat for the large prey mammals of tigers. These results will inform future wildlife In future plans to restore the populations of large prey mammal species of tiger, research is increasingly identifying prey availability as a significant limitation to tiger recovery across its range in Thailand; tiger prey populations augmentation is seen as an important catalyst that may accelerate recovery (Jornburom et al, 2020;Phoonjampa et al, 2021;Phumanee et al, 2021). Therefore, the Mun Sam Ngam area could be used as a model for other areas of dry evergreen forest, because this habitat has a high abundance of the large prey mammal species.…”
Section: Discussionmentioning
confidence: 99%